Enhancing fish productivity through pen culture: a case study in Sareni wetland of Uttar Pradesh - Alam, A.; Joshi, K. D.; Das, S. C. S.; Jha, D. N.; Srivastava, K.; Kumar, V.; Bhattacharjya, B. K. (Indian Journal of Fisheries, 2018)
Pen culture for in situ raising of stocking material was conducted in Sareni Jheel, located in the Rae Bareli District of Uttar Pradesh. Higher values of silt (29%) and clay (15%) were recorded Sareni Jheel, being rich in organic carbon (4.5%) and nutrients. Rich oxygen levels, alkaline pH, high organic matter, moderate to high chemical parameters suggested moderately productive nature of this wetland. Pen with high-density polyethylene (HDPE) net was installed in area of 0.1378 ha and stocked with advanced fry of the Indian major carps, rohu Labeo rohita and catla Catla catla in the ratio of 1:1 @ 25 nos m-2. No significant changes in water quality parameters were noticed within and outside the installed pen. Mean weight at stocking of rohu and catla was 2.88±1.41 g and 2.1±1.16 g, which increased to 57.2±13.84 g and 67.38±25.79 g respectively, in 120 days. The average feed conversion ratio (FCR) recorded was 1.08 with overall survivability of 69.52% in rohu and 74.74% in catla. Benefit-cost ratio and return on investment were calculated as 1.69 and 0.69, respectively. Intervention through pen culture resulted in the increase in fish productivity of Sareni Jheel from 310 to 833 kg ha-1.